Impact of contrasting soils in a high-altitude vineyard of Vitis vinifera L. cv. Malbec: root morphology and distribution, vegetative and reproductive expressions, and berry skin phenolics - Mezzatesta, Daniela Silvia (2022)
The high-altitude viticulture of Mendoza is being increasingly recognized among the top wine regions worldwide. High levels of solar ultraviolet-B (UV-B) radiation, alluvial heterogeneous soils and cool night temperatures are major influences on Vitis vinifera L. phenotypic characteristics, especially on Malbec, Argentina?s emblematic grapevine variety. In the present work, the effect of intra-vineyard contrasting soil depth on Malbec was evaluated in a high-altitude vineyard (1450 m a.s.l.), over two growing seasons for physiological traits and over three vintages for yield components and berry skin phenolic compounds. The experiment was carried out in two parcels of shallow (SS) and deep (DS) soils, with different physico-chemical characteristics, submitted to equal irrigation and crop management. Results showed that root depth was not limited by any soil physical constraints and fine roots (< 1 mm) were patchily distributed in sites with higher contents of silt, clay and organic matter in SS. Higher root quantity in SS was related to lower vegetative and reproductive expressions, shorter ripening period, and reduced berry size and fruit yield, as compared to DS. When SS plants experienced mild water stress (ΨS, stem water potential, between -6 to -9 bar) increments of anthocyanins, total polyphenols and antioxidant capacity in berry skins were observed. However, when SS plants reached ΨS ≤ -10 bar, physiological harm occurred. The results presented contribute to understand the effects of soil type on Malbec vines during different seasonal environmental conditions, especially in stressful conditions such as those expected by climate change scenarios.